A new Annonaceae genus, Wuodendron, provides support for a post–boreotropical origin of the Asian–Neotropical disjunction in the tribe Miliuseae. Issue 2 (20th December 2017) - Xue, Bine; Tan, Yun-Hong; Thomas, Daniel C.; Chaowasku, Tanawat; Hou, Xue-Liang; Saunders, Richard M.K.
Abstract: Recent molecular and morphological studies have clarified generic circumscriptions in Annonaceae tribe Miliuseae and resulted in the segregation of disparate elements from the previously highly polyphyletic genus Polyalthia s.l. Several names in Polyalthia nevertheless remain unresolved, awaiting assignment to specific genera, including Polyalthia litseifolia. Phylogenetic analyses of seven chloroplast regions (atpB–rbcL, matK, ndhF, psbA–trnH, rbcL, trnL–F, ycf1; ca. 8.3 kb, 116 accessions, including representatives of all currently accepted genera in subfamily Malmeoideae) unambiguously placed Polyalthia litseifolia in a clade with three accessions from Thailand, which have previously been shown to represent an undescribed genus sister to the Neotropical clade (Desmopsis, Sapranthus, Stenanona, Tridimeris) in the predominantly Asian tribe Miliuseae. The collective clade is sister to Meiogyne. Polyalthia litseifolia shares several diagnostic characters with most species in the Neotropical genera and Meiogyne, including: petals that are similar in shape and size in both whorls; multiple ovules per ovary in one or two rows; and lamelliform endosperm ruminations. It is distinct in being deciduous, bearing subpetiolar buds and having inflorescences growing from the leaf scar of the dropped leaves. Morphological comparisons and phylogenetic analyses corroborate its recognition as a new genus, which is formally described and illustrated here as Wuodendron. Polyalthia litseifolia is furthermore found to be conspecific with Desmos praecox, and the latter name is used as the basis for the name of the type. Molecular divergence time estimates under an uncorrelated lognormal relaxed clock place the Wuodendron–Neotropical clade split within the Miocene (ca. 14–12 Ma), highlighting the importance of post–boreotropical dispersal and vicariance in shaping intercontinental tropical disjunctions in Annonaceae.